Jumbo rates below conforming rates: When did this happen and why? - Stephen D. Oliner; Tobias Peter; Lynn M. Fisher; Mike Fratantoni (American Enterprise Institute (AEI), 2020)
The authors find that the shift reflects a combination of increased bank demand for jumbo loans and higher government-sponsored enterprise g-fees.
Keywords: A; 330; GSEs (Fannie Mae and Freddie Mac); Housing Center: Research; economics